1968
DOI: 10.1243/jmes_jour_1968_010_036_02
|View full text |Cite
|
Sign up to set email alerts
|

Side Thrust Control by Secondary Gas Injection into Rocket Nozzles

Abstract: Directional control of rockets can be achieved by using secondary gas jets for providing side forces. The present investigation is concerned with the fact that a greater side force can be achieved by expanding the secondary gas into the supersonic region of the main nozzle than by expanding it directly to atmosphere. A laboratory test rig using ambient temperature air for the primary and secondary flows is described. Axial thrust and side force were measured using strain gauge force transducers. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1970
1970
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…With further increase in injection, C AV decays. This complies well with [23] and in [44] on 2-D nozzle slot injection, where a higher injection-performance ratio is noticed for the injection rate ratios between two and four.…”
Section: B Gas Flow Properties 1 Secondary Flow Conditionssupporting
confidence: 88%
See 1 more Smart Citation
“…With further increase in injection, C AV decays. This complies well with [23] and in [44] on 2-D nozzle slot injection, where a higher injection-performance ratio is noticed for the injection rate ratios between two and four.…”
Section: B Gas Flow Properties 1 Secondary Flow Conditionssupporting
confidence: 88%
“…Compared to the fundamental cases of slot and circular sonic injections at the flat plate, the secondary injection inside a rocket nozzle is distinguished by the strong wall-bounded supersonic crossflow character, as was also reported in [20][21][22][23][24]. The internal effects of the lateral sides of the wall and the possible main shock reflection further affect the complex interaction crossflow field.…”
Section: Nomenclaturementioning
confidence: 81%
“…The nozzle was attached to a thrust rig described in detail in ref. 1. The side force was measured using a Strain gauge transducer and the arrangement was such that side force could only be measured in a vertical plane containing the main nozzle axis.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…Shigeru Aso et al [14] showed that, for slotted injection, the effect of aerodynamic fences has to be considered. Neilson et al [15] studied the effect of fluidic injection in rocket nozzles and Louis A. Cassel [16] studied the response of aircraft under an ambient atmospheric environment. Bernhard Stahl and Helmut Esch [17] experimentally measured the wall pressures for distinct flow injection setups.…”
Section: Introductionmentioning
confidence: 99%